You are walking down a road seeking treasure the real branches of into 3 paths a guard stands in each path you only know that only one of the girls is telling the truth and the other two are lying this is what they say guard one the treasure lies down this path guard to no treasure lies down this path seek elsewhere Garth 3 the first guard is lying

Answers

Answer 1
Answer:

Answer:

Guard Two

Step-by-step explanation:

Guard two has the path to the treasure because he's telling people that there's no treasure. That makes him suspicious because he might want the treasure for himself

Answer 2
Answer:

Final answer:

This is a logic puzzle wherein the guards' statements are evaluated based on the given criteria: only one guard is truthful. Upon analysis, we find that only the path guarded by Guard 2 aligns with this criteria, indicating that this is the path you should take to find the treasure.

Explanation:

This is a classic logic problem, often called the 'Liar and Truth-Teller' puzzle. Here's how we can tackle it:

Guard 1 says: 'The treasure lies down this path.'

Guard 2 says: 'No treasure lies down this path, seek elsewhere.'

Guard 3 says: 'The first guard is lying.'

Since we know that only one guard is telling the truth, let's consider if Guard 1 tells the truth. If so, Guard 2 and Guard 3 would be lying, which contradicts the statement of Guard 3 (who confirms Guard 1's statement as a lie).

If Guard 2 is telling the truth (which means there's no treasure on his path), then both Guard 1 and Guard 3 would be lying, which fits our criteria.

If Guard 3 told the truth, this would mean that Guard 1 is lying, but then Guard 2 would also be telling the truth--this contradicts our initial information (only one guard is truthful).

So, based on these evaluations, you should take the path guarded by Guard 2 because he's the only one telling the truth according to the given criteria.

Learn more about Logic Puzzle here:

brainly.com/question/15483103

#SPJ2


Related Questions

Identify the GCF of 12a^4b^3 + 8a^3b^2. 4a^3b^2 2a^3b 4a^2b 8a^3b^2
How many inches are in 4 feet 3 inches?
Create and solve a linear equation that represents the model, where circles and a square are shown evenly balanced on a balance beam.A. x + 10 = 6; x = -4B. x = 6 + 10; x = 16C. x + 6 = 16; x = 10D. x + 6 = 10; x = 4
Calculate the total cost of an item bought at a negotiated price of $15,640 and a $2,500 trade-in allowance. The sales tax is 7.2 with a $106 registration fee.$13,160 $14,372.08 $1,232.08 $14,286.08
In the first 3 days of class, daunte lost 2 pencils. if daunte keeps losing pencils at the same rate for 60 days of class,how many pencils will he lose

Of the flowers on Jill's front lawn,2/5 are tulips. Of the tulips,5/8 are yellow. What fraction of the flowers on Jill's front lawn are yellow tulips. A 18 B 1/4 C 1/2 D 7/13

Answers

2/5 of the flowers are tulips, 5/8 of the tulips are yellow. Yellow tulpis are 5/8 of 2/5 of the flowers.

(5)/(8) \ of \ (2)/(5)=(5)/(8) * (2)/(5)=(1)/(8) * (2)/(1)=(2)/(8)=\boxed{(1)/(4)} \Leftarrow \hbox{answer B}

Answer:

1/4

Step-by-step explanation:

A prism has a surface area of 350 mm2.Find the surface area of a scaled image with a scale factor of 2.

Answers

Just put an exponent of '2' on the scale factor and multiply it by the surface area.

Scale factor = 2

\sf2^2\rightarrow4

Multiply it:

\sf350*4=1400~mm^2
You would mulitply the factor by itself
2^2 = 4

then you would multiply the surface area by 4 

350 x 4 = 1400 mm^2

Answer 1400 mm^2

For a standard normal distribution, which of the following expressions must always be equal to 1?A) P(z≤-a)-P(-a≤z≤a)+P(z≥a)
B) P(z≤-a)-P(-a≤z≤a)+P(z≥a)
C) P(z≤-a)+P(-a≤z≤a)-P(z≥a)
D) P(z≤-a)+P(-a≤z≤a)+P(Z≥a)

Answers

P(z ≤ -a) + P(-a ≤ z ≤ a) + P(z ≥ a) = 1 - P(z ≤ a) + [P(z ≤ a) - P(z ≤ -a)] + 1 - P(z ≤ a) = 2 - 2P(z ≤ a) + P(z ≤ a) - [1 - P(z ≤ a)] = 2 - P(z ≤ a) - 1 + P(z ≤ a) = 1

Therefore, option D is the correct answer.

Answer:

D. P(z\le -a)+P(-a\le z\le a)+P(z\ge a)

Step-by-step explanation:

Properties of normal distribution-

  1. The normal curve is symmetrical about the mean (μ).
  2. The mean is at the middle of the graph and it divides the area into two equal halves.
  3. The total area under the curve is equal to 1.

The total area under the curve can be divided into parts like,

  1. area below -a, i.e z\le -a,
  2. area between -a to a, i.e -a\le z\le a
  3. area above a, i.e z\ge a

Therefore, P(z\le -a)+P(-a\le z\le a)+P(z\ge a)=1

Turner's scores for nine video games are 140, 180, 200, 170, 180, 150, 160, 130, and 121. The mean, median, and mode of his scores are given below.mean = 159
median = 160
mode = 180
Which value gives Turner's game average?

Answers

Answer:

The mean gives Turner’s game average.

Step-by-step explanation:

The median describes the number in the middle from lowest to greatest. The mode describes the number that appears the most. The mean describes the average of the data set.

a farmer has 1235 trees to be planted on a rectangular parcel of land. if there are 24 trees planted in each row and each row must be completed before it is planted, how many trees will be left over after planting?

Answers

The required number of trees that were left over after planting is 11.

Given that,
A farmer has 1235 trees to be planted on a rectangular parcel of land. if there are 24 trees planted in each row and each row must be completed before it is produced, how many trees will be left over after planting is to b determined.

What is arithmetic?

In mathematics, it deals with numbers of operations according to the statements.

Total number of trees = 1235
Total numbers of trees in a row = 24
Number of trees left = quotient + remainder / divisor
                               = 1235/24
                               = 51 + 11 / 24

Thus, the required number of trees that were left over after planting is 11.

Learn more about arithmetic here:

brainly.com/question/14753192

#SPJ2

24 trees per row
1235 trees to plant

1235 / 24 = 51 remainder 11

There will be 11 trees left over

X • x = 2x need help

Answers

x\cdot x=2x\nx^2-2x=0\nx(x-2)=0\nx=0 \vee x=2
x*x=2x \n x^2=2x \n x^2-2x=0 \n x(x-2)=0 \n x = 0  \ \ \ \vee  \ \ \ x-2=0 \ therefore \ x= 2